PENERAPAN PROTOKOL KESEHATAN BAGI SISWA SEKOLAH DALAM MENCEGAH PENULARAN COVID-19 - Paramasatiari, A.A.A.L.; Widhidewi, N.W. (Buletin Udayana Mengabdi, 2024)
In March 2021, Covid-19 cases began to decline until the number of sufferers was below 100 people. Education plays a crucial role in the intellectual life of the nation and state. During the Covid-19 pandemic, the education process is carried out online using Zoom, Google Classroom or through groups on Whatsapp. At the time of conducting interviews in this study, not all teachers had received vaccinations and were still waiting for their schedule for it. SD Negeri 17 Dauh Puri has more than 500 students and 39 teachers. Teachers only obtained information regarding Covid-19 preventions from news on television. Thus, they need training and assistance in preparing health protocols that must be adhered to when offline learning takes place. Teachers have a very important role in implementing health protocols in schools. In preparing for offline learning, strict health protocol flows need to be drawn up so that the transmission of the Covid-19 virus in schools can be prevented. As a solution to the problems that will be found in the preparation of offline learning, a Focus Group Discussion (FGD) has been conducted to find out the teacher’s understanding of the implementation of protocols in schools, discussions have been carried out regarding the determination of the flow of health protocols in schools, and the assistance of personal protective equipment and facilities as well as infrastructure that are useful in implementing health protocols is provided. The output targets of the study are an increase in understanding of health protocols for teachers by 80 percent, the establishment of health protocol flows in the schools and the availability of facilities related to health protocols in schools.  Keywords: Elementary School, Health Protocols, Covid-19, Offline learning